Biliary reconstruction with or without an intraductal removable stent in liver transplantation: study protocol for a randomized controlled trial. Issue 1 (December 2015) - Goumard, Claire; Cachanado, Marine; Herrero, Astrid; Rousseau, Géraldine; Dondero, Federica; Compagnon, Philippe; Boleslawski, Emmanuel; Mabrut, Jean; Salamé, Ephrem; Soubrane, Olivier; Simon, Tabassome; Scatton, Olivier
Abstract Background The incidence of biliary complications following liver transplantation (LT) remains high, ranging from 10 to 50 % of patients, especially when the diameter of the bile duct is smaller than 7 mm. Biliary reconstruction is most often performed by duct-to-duct anastomosis. In a preliminary study (n = 20), we previously reported a technique of biliary reconstruction using an intraductal stent tube followed by its endoscopic removal and showed both the feasibility and safety of this innovative procedure. The next step is to validate the potential benefit of this procedure in a randomized controlled trial. Design This is a multicenter randomized controlled trial in France comparing the efficacy of biliary reconstruction with or without a removable intraductal stent on reducing biliary complications. Inclusion and randomization are performed during LT when a duct-to-duct biliary anastomosis smaller than 7 mm in diameter is envisioned. In the intraductal stent group, a custom-made segment of a T-tube is placed into the bile duct and removed endoscopically 4 to 6 months later. The surgical technique is described in a video during randomization and is available on the secure website used for inclusion and randomization. The primary endpoint is the occurrence of biliary complications, including biliary fistulae and strictures, during the 6 months of follow-up. Secondary evaluation criteria are the incidence of complications related to the stent placement and its extraction by endoscopy. The inclusion of 248 patients in total has been determined based on an expected incidence of biliary complications of 25 % in the non-IST group and a 60 % reduction of biliary complications (10 %) in the IST group. Discussion Biliary complications following LT are significant causes of morbidity, retransplantation, and mortality. Although controversial, the use of a T-tube has been proven to be useless and even responsible for specific complications related to the external part of the tube in many studies, including several randomized trials. However, several studies have identified a small bile duct diameter as a risk factor for biliary stenosis. A threshold of 7 mm was found to be significantly associated with biliary stenosis. Our team published a preliminary study that included 20 patients using a new technique of intraductal stenting. Only four complications were reported in the overall study population, whereas no biliary complication occurred in the subgroup of patients who received a whole graft LT. Moreover, no technical failures and no procedure-related complications were noted before and during the drain removal. Although an intraductal stent tube in duct-to duct biliary anastomosis seems feasible and safe, a multicenter randomized controlled trial is needed to validate its benefit as a protective tool against the occurrence of biliary complications. One original aspect of this protocol is the video demonstration of the surgical procedure, which is available on the web to standardize and homogenize the technique. The surgical community may be inspired by this type of tool in the future to minimize technical bias related to technical issues. Trial registration NCT02356939, date of registration 2 February 2015.